Sex Differences of Acute Stroke Treatment and in Hospital Outcomes After Intravenous Thrombolysis in Patients With Ischemic Stroke - Cai, Bin; Li, Sheng-de; Li, Hang; Liu, Zhen-qian; Peng, Bin (Frontiers in Neurology, 2020)
Background: Many studies have suggested that the clinical features of male patients with ischemic stroke are different from those of female patients, but related data on Chinese patients are scarce. Therefore, this study aimed to identify the differences in treatment delays, complications related to intravenous thrombolysis, and prognosis between male and female patients with ischemic stroke in China. Methods: The data of patients with ischemic stroke who received intravenous thrombolysis were retrospectively analyzed. The data were obtained from the China Hospital Stroke Registry from January 2017 to April 2019. The general clinical characteristics, onset-to-door time, door-to-needle time, complications related to thrombolysis, National Institute of Health Stroke Scale (NIHSS) scores, and in-hospital mortality were compared between male and female patients to identify any sex differences in these factors. A multi-factorial analysis was conducted to explore whether sex is associated with in-hospital mortality and complications of intracerebral hemorrhage after thrombolysis. Results: A total of 26,475 patients with ischemic stroke who received intravenous thrombolysis were involved in the study. The data were collected from 902 hospitals in 29 provinces, autonomous regions, and municipalities in China. The door-to-needle time was longer in female than in male patients (49 [35, 67] vs. 48 [35, 65], P=0.008). Furthermore, the frequencies of intracerebral hemorrhage (4.1% vs. 3.2%, P<0.001) and in-hospital mortality (2.55% vs. 1.83%, P<0.001) were higher in female vs. male patients. However, sex was not associated with intracerebral hemorrhage and in-hospital mortality according to the adjusted multi-factorial analysis. In addition, improvement in NIHSS scores was greater in female patients than in male patients [-3(-6,-1) vs. -3(-5,-1), P=0.036]. Conclusions: After adjusting for other predictors sex was not associated with intracerebral hemorrhage after thrombolysis or in-hospital mortality. Female patients exhibited greater improvement in symptoms than did male patients. Further study is warranted to evaluate the long-term outcomes in the different sexes.